Characterization of the Catalytic Subunits of the RNA Exosome‐like Complex in Plasmodium falciparum - Jiang, Ning (John Wiley and Sons Inc., 2018)

(untitled) (J Eukaryot Microbiol)
The eukaryotic ribonucleic acid (RNA) exosome is a versatile multiribonuclease complex that mediates the processing, surveillance, and degradation of virtually all classes of RNA in both the nucleus and cytoplasm. The complex, composed of 10 to 11 subunits, has been widely described in many organisms. Bioinformatic analyses revealed that there may be also an exosome‐like complex in Plasmodium falciparum, a parasite of great importance in public health, with eight predicted subunits having high sequence similarity to their counterparts in yeast and human. In this work, the putative RNA catalytic components, designated as PfRrp4, PfRrp41, PfDis3, and PfRrp6, were identified and systematically analyzed. Quantitative polymerase chain reaction (QPCR) analyses suggested that all of them were transcribed steadily throughout the asexual stage. The expression of these proteins was determined by Western blot, and their localization narrowed to the cytoplasm of the parasite by indirect immunofluorescence. The recombinant proteins of PfRrp41, PfDis3, and PfRrp6 exhibited catalytic activity for single‐stranded RNA (ssRNA), whereas PfRrp4 showed no processing activity of both ssRNA and dsRNA. The identification of these putative components of the RNA exosome complex opens up new perspectives for a deep understanding of RNA metabolism in the malarial parasite P. falciparum.